ASSESSMENT OF THE EFFECTIVENESS OF MULTISLICE COMPUTED TOMOGRAPHY (MSCT) IN THE DIAGNOSIS OF THORACIC ORGAN DISEASES IN MILITARY PERSONNEL (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article analyzes the role of multislice computed tomography (MSCT) in the diagnosis of chest diseases and injuries in military personnel. The high diagnostic value of MSCT in military medical settings is substantiated, where rapid decision-making, imaging accuracy, and dynamic patient monitoring are crucial. The diagnostic capabilities of MSCT in chest trauma are examined, including penetrating injuries, rib fractures, pneumothorax, hemothorax, pulmonary contusion, and the development of acute respiratory distress syndrome. Particular attention is given to the use of MSCT in infectious lung diseases, including atypical pneumonia, as well as in bullous emphysema and spontaneous pneumothorax in young individuals of military age. The method enables detection of minimal structural changes in lung parenchyma, three-dimensional reconstruction of injuries, and effective follow-up assessment. The study concludes that MSCT represents a key imaging modality in military medicine due to its high sensitivity and comprehensive diagnostic capabilities.
Keywords: Multislice computed tomography (MSCT); chest trauma; pneumothorax; hemothorax; pneumonia; bullous emphysema; military personnel; military medicine.